Effectiveness of Cognitive Restructuring on Depressed Mood in Girls with Self-Injury - Masoumeh Ali Mirzaee; Mahmoud Borjali; Nader Monirpour (Iranian Journal of Educational Research)
Objective: The primary objective of this investigation was to examine the efficacy of cognitive restructuring training on alleviating depressive symptoms in adolescent females exhibiting self-injurious behaviors. Methods: The methodological framework employed was a semi-experimental design incorporating pre-test, post-test, and follow-up assessments alongside a control group. The statistical population for this inquiry comprised all female students aged 15 to 18 years exhibiting self-injurious behaviors within the educational institutions of Baharestan city in 2023. A sample of thirty-six individuals who had engaged in self-injury within the preceding six months and had sought assistance from counseling clinics was selected through convenience sampling and subsequently allocated to experimental and control groups in a random manner. To facilitate data collection, the Beck Depression Inventory (BDI) and the ISAS Self-Injury Test were employed. The experimental group participated in eight sessions of cognitive restructuring training intervention, each lasting 90 minutes, while the control group received no intervention, followed by a one-month follow-up period. Data analysis was conducted utilizing multivariate analysis of covariance. Results: Following a thorough examination of the assumptions pertinent to multivariate analysis of covariance, the outcomes of paired comparisons among the mean differences across the three assessment stages indicate that within the cognitive restructuring group, the change in mean scores from the pre-test stage to both the post-test and follow-up stages is statistically significant (p<0.01). Conversely, the difference in scores between the post-test stage and the follow-up stage did not reach statistical significance (p<0.05). In the control group, the differences observed between the pre-test scores and both the post-test and follow-up stages, as well as the differences between the post-test and follow-up scores, were likewise not statistically significant (p<0.05). Conclusions: Consequently, it can be inferred that cognitive restructuring has demonstrated efficacy in mitigating depressive symptoms among adolescent females who engage in self-injury.